Progress on Tripterygium wilfordii Hook f. as a treatment option for neurodegenerative diseases - Zhong-mou Zhang; Tian-tian Zuo; Ming-hui Chen; Cai-xia Zang; Yong-jian Wang; Ya-dan Wang; Shuang-cheng Ma (Pharmacological Research - Modern Chinese Medicine, 2024)
Introduction: Neurodegenerative diseases are becoming increasingly widespread as the global population ages. Although neurodegenerative diseases have received continued attention from researchers, there are currently no drugs that can reverse the progression of these diseases. Tripterygium wilfordii Hook f., a traditional form of Chinese medicine, has been widely used to treat many diseases due to its numerous bioactivities and shows considerable potential for the improvement of neurodegenerative diseases. Methods: Articles for this review were searched on Pubmed, Scifinder, CNKI and Web of Science. Keyword included “Tripterygium wilfordii and neurodegenerative disease,” “triptolide and neurodegenerative disease,” “celastrol and neurodegenerative disease,” and “tripchlorolide and neurodegenerative disease.” 178 articles were initially retrieved and 119 articles were cited finally. Results: In this study, we summarize the progress of T. wilfordii, especially its bioactive components such as triptolide, celastrol and tripchlorolide for the treatment of neurodegenerative diseases and review the therapeutic mechanisms involved. This article provides reference guidelines for the use of T. wilfordii to treat neurodegenerative diseases. Discussion: The bioactive components like triptolide, celastrol, tripchlorolide and others extracted from T. wilfordii has enormous potential in the treatment of neurodegenerative diseases. However, the vague pathogenic mechanisms underlying neurodegenerative diseases, as well as toxicity and side effects of T. wilfordii on clinical use still exist. Further research is needed to investigate these issues.